Analisis Penentuan Kebutuhan Tempat Penampungan Sementara (TPS) Berbasis Unit Spasial Desa Studi Kasus Kota Yogyakarta - Sardi; Setiawan, Pandri; Achmad, Nizar (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2025)
Yogyakarta is a popular tourist destination for domestic and foreign tourists. The high number of tourists visiting each year has a positive impact on the city's economy, by increasing tourism sector income and creating job opportunities for the local community. However, this increase in tourist activity also causes environmental problems, especially related to the increase in waste volume. The increasing number of tourists visiting Yogyakarta is directly proportional to the increase in waste production, both organic and inorganic, which comes from various types of waste, such as food and drink packaging, as well as other plastic and non-plastic waste. In recent years, the waste problem in Yogyakarta City has become a serious issue that requires immediate handling. This research uses descriptive quantitative methods consisting of calculating population estimates, calculating TPS needs, and making maps. determining the distribution and calculation of TPS needs refers to SNI 19-2452-2002. The aim of this research is to determine the distribution of polling stations in the city of Yogyakarta using a geographic information system (GIS). Based on calculation results, the City of Yogyakarta, which has 14 sub-districts and 45 sub-districts, has 2 3R TPS (1 operating and 1 in the construction stage) and 14 Transfer Depots. Meanwhile, the required communal TPS is 155 units.